Equity-Focused Palliative and End-of-Life Care in a System Not Designed for it: Qualitative Insights from Service Providers and Recipients - Courtney R. Petruik; Lauren Wan-Sai-Cheong; Helen Hagos; Katrina Milaney (Global Qualitative Nursing Research)
‘Equity-focused care’ has gained attention in recent years. With widespread use, concepts take on different meanings creating confusion for service providers. This study examines what people experiencing homelessness with life-limiting illnesses value in equity-focused care, and how service providers—who identify their work as equity-focused—describe their roles within a care system that relies on, yet often undervalues, this kind of work. We conducted 11 interviews with service providers and seven with people experiencing homelessness with a life-limiting illness and who received care from a community-based palliative care team in Western Canada. Interviews were transcribed and analyzed via thematic analysis. We constructed three themes: Adapting to Individual Needs; Service Provider Orientation to Practice ; and Being Present with People . Themes aligned with two spheres of influence from the Education Training Research’s Health Equity Framework: Relationships and Networks and Systems of Power . Findings highlighted that service providers deliver equity-focused care by developing strong relational care networks challenging existing power structures –making this model incongruent with existing individually-focused biomedical care models. Findings transform the theoretical concept, ‘equity-focused care’, into tangible knowledge that highlights areas for policy change to support equity-focused care.